A Comparison of Methods for Portraying School Demography Using Census Data - Nagy, Philip; Traub, Ross E.; Moore, Shawn (Alberta Journal of Educational Research, 1999)
Several ways of indexing the demography of a school from Canadian census data were devised and compared. In one comparison, statistics based on the complete catchment area of a school were set against statistics specific to the neighborhoods inhabited by the students actually attending the school. In a second comparison, catchment-area statistics, which were based on the total population in the area, were compared with statistics based on the subpopulation of mothers of school-aged children residing in the area. The results indicate that the methods are not interchangeable, although the degree of discrepancy observed between methods varied with the demographic variable considered. The demography-indexing methods were also compared for degree of correlation with student achievement in language or mathematics. The demographic indicators obtained using the enrollment method were found to correlate a little more strongly with achievement than the indicators obtained using the catchment area method. All results are merely suggestive, however, pending further study.